Evaluation of Environmental Factors and Morphological Characteristics of Microorganisms in the Utcubamba Bagua-Amazon River - Ajrota, Victor Cipriano Huanacuni; Quispe, Maria Foraquita; Foraquita, Sosueth Mary Dayine Huanacuni; Foraquita, Luzmar Clareth Huanacuni; Ramos, Julio Rumualdo Gallegos (Journal of Posthumanism, 2025)
The objective of this study is to determine the environmental factors and morphological characteristics of the free-living microorganisms of the Utcubamba River, a study that was carried out along the Utcubamba River from the sampling point: Puente Bagua Grande, Trayec1, Bagua Chica, Dist Milagros1, Milagros2 of the Amazonas Region Peru. Using the quantitative and descriptive methodology, data collected in situ such as T°, pH, E.C., TDS, Salinity and the morphological characteristics of microorganisms divided into free-living groups determined in the laboratory of the University and as an environmental instrument, the ECAs of water for rivers were used; carried over a period of six months. As a result, the pH fluctuates between 8.98 found in the Milagros River1 and 7.45 recorded under Puente Bagua Grande with an average of 8.30. The maximum temperature is 27.7 °C recorded in the Bagua Chica River and the minimum is 21.5 °C obtained in the Milagros River2 with an average of 24.5 °C. C.E. fluctuates between 490 mmhos/cm recorded in the Bagua Chica River and 139.2 mmhos/cm obtained in the Puente Bagua Grande River with an average of 331.3 mmhos/cm. TDS fluctuates between 342 mg/l obtained in the Bagua Chica River and 97.3 mg/l found in the Puente Bagua Grande site with an average of 232.3 mg/l; Salinity fluctuates from 0.00 to 0.2 g/l which is obtained in the 05 sampling points with an average of 0.18 g/l and in characterization of the microorganisms there is in the Group of Protozoa: Vorticella, Paramecium, Amoeba, Tetrahymen, Group of Algae: Euglena, Cosmarium, Diatomaceae, Zygnema and in Metazoan Group: Daphnia, Rotiferos is observed in all samplings. Scianoficeae Group: Spirulina, Nostoc sp, Oscillatoria; Chlorophyta Group: We only have Pediastrum. In conclusion, in the analysis of variance in the environmental parameters for the aforementioned places, the interpretation in Rows does not exist significant difference and for columns there is a highly significant difference, therefore, the hypothesis is rejected.